EVALUASI PROGRAM BANTUAN RUMAH LAYAK HUNI (MAHYANI) DI DESA PUNCAK MANDIRI KECAMATAN SUMALATA KABUPATEN GORONTALO UTARA - Baderan, Umar Sako; Gintulangi, Sri Lestari; Lonteng, Marcellia Simon (Gapenas Publisher, 2024)
This study aims to evaluate the implementation of the Decent Housing Assistance Program (Mahyani) in Puncak Mandiri Village, Sumalata District, North Gorontalo Regency. The research method used is a qualitative approach with descriptive research type. The data sources of the study include the Village Head, Village Secretary, Village Apparatus, as well as the recipients and non-recipients of the program. Data collection was conducted through observation, interviews, and documentation. The results of the study indicate that the implementation of the Mahyani Program in Puncak Mandiri Village still faces several challenges. Although the construction of Mahyani houses has begun, the construction process is still incomplete, and there are shortcomings in the transparency of program implementation by the village government. Furthermore, the main objective of this program, which is poverty alleviation, has not been fully achieved due to budget limitations and dependence on village funds. This study provides important insights for local governments, particularly in enhancing the effectiveness and transparency of social assistance program implementation. Better improvement measures are needed to ensure that assistance programs such as Mahyani can provide maximum benefits to the communities in need